Effective Defense of Aleppo Pine Against the Giant Scale Marchalina hellenica Through Ecophysiological and Metabolic Changes - Fotelli, Mariangela N.; Lyrou, Fani G.; Avtzis, Dimitrios N.; Maurer, Daniel; Rennenberg, Heinz; Spyroglou, Gavriil; Polle, Andrea; Radoglou, Kalliopi (Frontiers in Plant Science, 2020)
Aleppo pine (P. halepensis) is distributed in the Mediterranean region and in other areas of the world, where it has been introduced due to its adaptive capacity to xerothermic conditions. The giant pine scale M. hellenica often infests Aleppo pine and pines, in southeastern European countries, causing pine declines. When combined with the expected intensified heat and drought events in eastern Mediterranean, the impact of this biotic parameter on the host pines may be exacerbated. The importance of understanding the defense mechanisms of Aleppo pine is emphasized by the recent invasion of the pine scale in new regions, like Australia, lacking the insect’s natural enemies, where intenser impacts on pine species may occur. To date, Aleppo pine’s physiological responses to the infestation by M. hellenica are largely unknown. This study aimed at assessing the responses of Aleppo pine to the giant pine scale attack, both on an ecophysiological and a metabolic level. Gas exchange, needle water status and carbon and nitrogen content were measured during one year on healthy and infested adult trees. Μetabolic profiling of Aleppo pine needles was also performed before, during, and after the high feeding activity of the insect. The maintenance of stable relative water content, δ13C signatures and chlorophyll fluorescence in the needles of infested pines indicated that infestation did not induce drought stress to the host pines. At the peak of infestation, stomatal closure and a pronounced reduction in assimilation were associated with the accumulation of sugars in the needles, probably due to impaired phloem loading. At the end of the infestation period, tricarboxylic acids were induced and phenolic compounds were enhanced in the needles of infested pines. These metabolic responses, together with the recovery of photosynthesis after the end of M. hellenica intense feeding, indicate that in the studied region and under the current climate Aleppo pine is resilient to the infestation by the giant pine scale. Future research should assess whether these promising defense mechanisms are also employed by other host pines, particularly in regions of the world recently invaded by the giant pine scale, as well as under more xerothermic regimes.